Transforming space : visible and invisible changes in premodern European cities. - Abrahamse, Jaap Evert; Deneweth, Heidi (Turnhout : Brepols, 2022)
Essays on the often-ignored spatial dynamism of pre-modern towns: about urban space gradually or radically adapting to the changing conditions of city life.00'Transforming Space' deals with visible and invisible changes in pre-modern cities, their causes and the way in which they were perceived and received. The chapters in this book analyse the development and management of urban space, combining case studies and insights from a range of cities from all over Europe. Several contributions deal with the impact of major events on the urban tissue: geopolitics; disasters such as fires or wars; expropriation or redevelopment projects directed by urban governments; religious change such as the Dissolution in England, and the Reformation and Counter-Reformation on the continent. On closer scrutiny, however, some of these major events were only an accelerator of already ongoing processes of change. By shifting the perspective from the city as a whole, to neighbourhoods, urban blocks or even plots of land, other chapters reveal how functional change or real estate dynamics changed the urban landscape almost imperceptibly. This book is written from a comparative perspective that takes into account path-dependency. Pre-existing power relations, ideology and mentality, the resilience of property structures, the impact of building regulations, subsidies, or the effects of real estate markets are shown to have had different outcomes for different social groups and the evolution of neighbourhoods.
boek
Keywords: Cities and towns -- Europe; Urbanization -- Europe